The Influence of Influencer Marketing and Viral Marketing on Glad2glow Product Purchase Decisions with Trust as a Mediating Variable - Novia Wardaningrum Isti Rahmawati Ashidiq; Ida Aryati DPW; Siti Maryam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of influencer marketing and viral marketing on purchasing decisions for Glad2Glow products, with trust as a mediating variable among Generation Z in Surakarta. The study used a descriptive quantitative approach with a purposive sampling technique on 80 Generation Z respondents who were familiar with Glad2Glow products. Data were collected through a questionnaire using a Likert scale and analyzed using the Partial Least Square (PLS) method using SmartPLS. The results showed that influencer marketing had a positive and significant effect on trust, and viral marketing also had a positive and significant effect on trust. Viral marketing was proven to have a positive and significant effect on purchasing decisions, while influencer marketing did not have a significant effect on purchasing decisions. In addition, trust did not have a significant effect on purchasing decisions. The results of the mediation test also showed that trust was unable to mediate the influence of influencer marketing or viral marketing on purchasing decisions. These findings indicate that for Glad2Glow skincare products, viral marketing strategies are more effective in driving purchasing decisions than influencer marketing, while consumer trust has not been a factor that directly determines purchasing decisions. This study provides implications for companies to optimize digital marketing strategies, especially through strengthening viral content that can increase consumer appeal and engagement.